EARLY VERSUS LATE EXTERNAL CEPHALIC VERSION - Akhtar, Nasim (Journal of Postgraduate Medical Institute, 2013)
Objective: To find out whether initiating external cephalic version (ECV) earlier in pregnancy increase therate of successful ECV procedures, and be more effective in decreasing the non cephalic presentations atbirth and also cesarean section rate. Methodology: This interventional study was conducted in Department of Obstetrics and GynecologyMardan Medical Complex from first July 2010 to 31st Dec 2011.It included women with singleton breechfetus at a gestational age of 34 to 35 weeks. Patients were randomly divided into two groups, those havinga first ECV procedure between 34(238 days) and 35 weeks of gestation were called early ECV group thesecond group included those who had first ECV at or after 37 weeks(259 days) and were called delayed ECV group. Percentages were calculated for qualitative variables like Gravida, complications etc, whilemean and SD for quantitative variables like gestational age. Results: Out of total 203 women who had breech presentation 123 were finally selected for the trial. EarlyECV group included 63 patients while delayed group included 60 patients..Fewer fetuses were in noncephalic presentation at birth in the early ECV group (41/63[65%] versus 29/60[49%] in the delayed ECVgroup, p = 0.04. There were no differences in rates of cesarean section (19/63[30%] versus 20/60 [33%],p=0.42) in the early ECV group versus the delayed ECV group. The rate of preterm birth was not differentbetween groups, early ECV group (2/63[3%] versus 0/60[o], p=o.26) delayed ECV group. Conclusion: External cephalic version at 34 and 35 weeks increase the likelihood of cephalic presentationat birth but it does not decrease the rate of cesarean sections and may increase the rate of preterm birth inthe early ECV group.